The Role of Resource Consumption Accounting in Achieving Competitive Advantage Applied Research: General Company for Textile and Leather Industry - Mustafa Waleed Zghair (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
The objective of this research is to explore resource consumption accounting within the economic unitunder study. Additionally, the research aims to analyze competitive advantage as a process ofuniqueness for an organization or a specific superiority when compared to its competitors. Based onthis, the researcher posits that sustainable competitive advantage refers to the organization's objectiveability to adapt to changes in the market environment and to thoroughly examine the industryenvironment. The research problem stems from the fact that many companies in today's world strive for leadershipand excellence in production through the recognition of the importance of modern systems, particularlyresource consumption accounting, in achieving competitive advantage. However, the challenges andexternal factors that accompany production processes may hinder this achievement. The studyinvestigates whether resource consumption accounting has an impact on competitive advantage. The research is based on the hypothesis that there is a significant correlation between resourceconsumption accounting and sustainable competitive advantage. The importance of the research lies inhighlighting the role of resource consumption accounting in achieving sustainable competitiveadvantage, and in assessing the impact of resource consumption accounting on the realization of suchan advantage.